Retrospective study of cases of rupture uterus at tertiary care center in Egypt - Ezzat, Laila; Salah, Mohamed (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Uterine rupture (UR)is one of the most serious obstetrical emergencies necessitating prompt diagnosis and management, as it en-dangers the maternal and fetal life. Uterine rupture (scarred/ unscarred) may occur at any stage of pregnancy. In developed countries, with good antenatal care and good supervision during labour, (UR) has become rare except by dehiscence of a caesarean scar. The objective of present study was to find out risk factors, management, related complications and associated maternal and fetal outcomes with rupture uterus. Methods: A retrospective study, data files and the case notes was retrieved from the medical records department at Aswan university hospital from January 1 2013 to December 31 2013 in the form of data relating to the age, parity, gestational age, method of termination, perinatal outcomes, and related maternal complications. Results: There were 4284 deliveries during the period under review among them 5 cases of uterine rupture. Thus, the incidence of uterine rupture was 1.1/1000 deliveries.3 cases (60%) of them had no antenatal care at any hospital or primary care center. The risk factors in these cases are in majority 4 (80%) of cases uterine rupture occurred in women with previous scar, 1case (20%) of cases uterine rupture occurred in women with none scarred uterus. As regard surgical management 3 cases (60%) managed by hysterectomy and 2cases (40%) managed by repair. As regard maternal and fetal outcome all women required blood transfusion. Associated bladder rupture was repaired in two cases (40%). After excluding fetal wastage before the age of viability, perinatal mortality was 100% (5/5). Conclusions: Present retrospective analytical study has concluded that rupture uterus is a life-threatening complication. Proper antenatal and intrapartum care, identification of high risk factors, promotion of skilled attendance at birth and institutional delivery are key factors in reduction and early diagnosis.